Development of Ultra High-Performance Concrete with Artificial Aggregates from Sesame Ash and Waste Glass: A Study on Mechanical Strength and Durability - Aïssa Rezzoug; Ali H. AlAteah; Muwaffaq Alqurashi; Sahar A. Mostafa (Buildings)
This study demonstrates the conversion of agricultural and industrial waste into construction materials by developing ultra-high-performance concrete using cold-bonded sesame ash and waste glass aggregates. The primary focus of this study was sustainability and waste valorization in self-curing concrete systems. This study focuses on many aspects of producing cementless concrete with superior short- and long-term properties, incorporating an innovative artificial aggregate premanufactured using sesame ash and waste glass. Prepacking technology of casting was used. A self-curing additive is used to reduce the energy required for curing. In cold-bonded aggregates (CBAs), the aggregate content ranged from 10 to 50% of the total sand volume. Polyethylene glycol was used as an internal curing agent to evaluate the mechanical properties of the concrete, including the compressive strength and tensile strength at different ages. The durability characteristics of the concrete were also analyzed in terms of its resistance to sulfates, chloride ion penetration, and performance at elevated temperatures of 300 and 600 °C. Microscopic analyses were conducted by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and Differential Scanning Calorimetry (DSC). The results showed a significant improvement in the mechanical and durability performance, especially at 30%, which resulted in the highest compressive strength of 147.2 MPa at 90 days. This is an 11.93% increase compared with that of the reference mix. The tensile strength was also improved by 14.5% at the same replacement ratio. The mix containing 30% manufactured aggregate demonstrated the best thermal resistance, retaining the highest percentage of residual strength at both 300 °C and 600 °C, as well as superior sulfate impact resistance, with a strength reduction factor of 39.5%. When the replacement ratio was increased to 50%, the chloride penetration resistance improved significantly by 41% compared with that of the reference mix. FTIR, TGA, and DSC analyses also demonstrated enhanced silicate polymerization and increased carbonate formation, contributing to the improved chemical stability and density of the concrete matrix.